Endometrioid Adenocarcinoma in the Native Ureter of a Renal Transplant Patient: Case Report and Review of the Literature - Kelly A. Healy; Kenneth J. Carney; Adeboye O. Osunkoya (The Scientific World Journal)
Endometriosis is characterized by endometrial-like tissue outside the uterus, primarily on the pelvic peritoneum, ovaries, and rectovaginal septum, and, in rare cases, within the urinary tract (1–3%). Although endometriosis is a benign condition, malignant transformation of endometriosis is a well-described phenomenon. Malignancies arising in endometriosis are uncommon at extragonadal pelvic sites. A case of endometrioid adenocarcinoma in the native ureter of a postmenopausal renal transplant patient presented with painless gross hematuria and hydroureteronephrosis. The patient had a history of total abdominal hysterectomy and bilateral salpingo-oophrectomy 14 years prior for menorrhagia and had since been on unopposed estrogen replacement therapy. Workup revealed a filling defect in the native left mid-ureter secondary to a large 2.5-cm ureteral tumor. Endoscopic biopsies of the native left ureteral mass showed endometrioid adenocarcinoma, grade II-III. The patient ultimately underwent an open native left nephroureterectomy and temporary diverting colostomy. Final pathology confirmed endometrioid adenocarcinoma, grade II-III, arising in a background of endometriosis with negative perirectal lymph nodes. This case of ureteral endometrioid adenocarcinoma highlights the importance of obtaining a careful history and maintaining a high index of suspicion for malignant degeneration, especially in the context of hyperestrogenism.